The Islamic Judiciary between Inheritance and Merit: A Historical Analysis of Egypt and the Levant (6–9 AH/12–15 AD) - Riad Salim Awad (Mazahib, 2026)
This study presents a critical historical analysis of the judicial institution in Egypt and the Levant during the period under examination. It seeks to derive insights relevant to contemporary judicial challenges. By tracing the evolution of the judiciary from the centralized Abbasid model to the doctrinal pluralism of the Mamluk era, the study demonstrates how judges appointed by political authorities maintained relative independence despite political pressure. Judges employed various mechanisms of resistance, including adherence to Sharia principles, resignation in protest, and reliance on public support. The study concludes that the effectiveness of the judicial system depended on a balance between three elements: judicial independence, societal oversight, and flexibility in managing doctrinal pluralism. It further argues that doctrinal pluralism, when regulated within a unified legal framework, can promote unity rather than division. Methodologically, the study relies on critical analysis of historical narratives through descriptive, comparative, and case-study approaches, enabling historical experiences to be linked to contemporary issues such as transparency and anti-corruption efforts. The study also identifies the positive and negative implications of hereditary judicial appointments.